The effects of TNF alpha inhibition of plasma fibrinolytic balance in patients with chronic inflammatory rheumatical disorders - (:unkn) unknown (My University, 2006)
Objectives. Recent studies support an inflammatory basis for atherosclerosis. Patients with chronic inflammatory rheumatical disorders are at increased risk for cardiovascular events, and this can be partially attributed to the inhibition of fibrinolytic system. TNF α inhibitors such as infliximab are shown to retard the progression of inflammatory arthritides. In this study, we investigated the effects of infliximab on plasma fibrinolytic parameters. Methods. Thirteen patients (7 female, 6 male; mean age: 44 ± 11 years) with a clinical indication for infliximab (rheumatoid arthritis (RA) (n = 8), ankylosing spondylitis (AS) (n = 5)) were selected. Plasma plasminogen activator inhibitor (PAI-1), tissue plasminogen activator (t-PA) antigens (Ag) and high sensitive C-reactive protein (hs-CRP) levels were measured during low salt intake at baseline. All patients received infliximab (Remicaide®, i.v. infusion, 3 mg/kg). Plasma PAI-1 Ag, t-PA Ag and hs-CRP were measured during low salt intake at the end of 2 weeks. All samples were collected at 9 AM. Antigen levels were determined using a 2-site enzyme-linked immunosorbent assay. Results. Patients experienced significant improvement in disease related activity scores after infliximab treatment. DAS score (for rheumatoid arthritis) and BASDAI index (for ankylosing spondylitis) decreased significantly after treatment (p = 0.01 and p = 0.04 respectively). Infliximab significantly reduced the marker of inflammation (hs-CRP) (8.3 ± 3.9 vs. 4 ± 4.1 mg/L, p < 0.01). Plasma PAI-1 antigen (64.7 ± 26.9 vs. 40 ± 31.1 ng/ml, p = 0.03) and PAI-1/t-PA ratio (10.8 ± 5.9 vs. 6.6 ± 3.8, p = 0.02) were significantly lower after the treatment. In contrast, plasma t-PA levels were unchanged (9.4 ± 4.4 vs. 9.0 ± 4.3 ng/ml, p = 0. 73). Conclusion. This study provides evidence that TNF α inhibition with infliximab decreases PAI-1 Ag level and PAI-1/t-PA ratio, and hence activates fibrinolytic system in patients with chronic inflammatory disorders. © Copyright Clinical and Experimental Rheumatology 2006.
Keywords: PaI-1; Plasma fibrinolytic balance; t-PA; TNF α inhibition